Work organization and time pressure among Finnish home care nurses: a cross-sectional study - Ruotsalainen, S; Väisänen, V; Pulkki, J; Sinervo, T (European journal of public health, 2025)
Abstract Background Due to a growing number of older people, nurses working in Finnish home care have been subject to increasing efficiency requirements leading to e.g., growing job demands, difficulties in recruitments, and turnover. Previous research has indicated that organizational factors, such as care continuity and self-organizing teams, can be beneficial for staff wellbeing and care quality. However, research incorporating workday characteristics remains scarce. The aims of this study were to examine (1) individual level work characteristics and job demands associated with time pressure among home care nurses, and (2) how time pressure varies at the organizational level and which factors might explain it. Methods A multi-source study, including a cross-sectional wellbeing survey for home care nurses and other data sources merged with the survey data. Linear regression analysis was used to analyze the association of time pressure and individual level variables. T-tests and ANOVA were used to analyze the differences in time pressure between organizational level variables. Results Shorter breaktime, lower care continuity, working alone, and disruptions during workday were associated with higher time pressure. Of the organizational level factors, teams with higher autonomy and where the Enterprise Resource Planning (ERP) system took teams into account when planning client visits, had lower time pressure. Conclusions To prevent increased workload, more flexibility is needed in home care nurses’ workdays. If an ERP system is used, it should ensure care continuity and more easily allow for changes if disruptions during the workday occur. Due to the independent nature of home care work, time for collegial support is also needed to cope with difficult situations. Furthermore, home care teams should have more autonomy over their work which might lead to higher satisfaction and retention among staff and facilitate recruitment. Key messages • A well-designed work organization, with sufficient flexibility, might alleviate time pressure among home care nurses. • Promoting care continuity and team autonomy could lead to improvements in employee wellbeing and satisfaction, resulting in higher retention among home care nurses.